Alicydohydrolase, and a method for producing the same
Patent Information
- Application Number
- CN202611121266.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-27
AI Technical Summary
然而,SAB属于强极性水溶性多酚酸类成分,脂溶性差、肠道膜通透性有限,口服后难以有效跨越胃肠道吸收屏障
1.本发明首次将甘草酸(GA)与丹酚酸B(SAB)通过分子间非共价键作用力共组装形成自组装纳米粒。其中,GA由亲水性葡萄糖醛酸基团和疏水性三萜苷元组成,作为自组装骨架;SAB作为被包载的水溶性酚酸类活性成分。二者通过氢键、静电作用及弱疏水相互作用自发形成稳定的纳米聚集体。经最优工艺制备的GS-NPs平均粒径为105.53±5.76 nm,PDI<0.292±0.007,粒径分布均一且体系稳定。傅里叶变换红外光谱法(FTIR)、X射线衍射法(XRD)及核磁共振氢谱(¹H-NMR)等表征结果证实二者通过氢键、静电作用等非共价键相互作用形成了稳定的纳米聚集体,SAB以无定形态分散于纳米粒中。GS-NPs对SAB的包封率为(77.70±0.86)%,载药量为(28.44±0.43)%,表现出较高的包载效率。不同于已有GA基共组装体系,本发明首次验证了水溶性酚酸类成分与GA共组装的可行性,填补了GA自组装递送体系在水溶性成分应用领域的技术空白。
Smart Images

Figure CN122973451A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomedical technology, specifically relating to a glycyrrhizic acid-tanstansine B self-assembled nanoparticle for myocardial protection during ischemia-reperfusion, its preparation method, and its application. Background Technology
[0002] Myocardial ischemia / reperfusion injury (MI / RI) is a common pathological process following acute myocardial infarction, coronary intervention, and thrombolytic therapy. It can induce multiple damages, including oxidative stress, inflammatory responses, mitochondrial dysfunction, and cardiomyocyte apoptosis, severely limiting the clinical efficacy of ischemic heart disease treatment. Salvianolic acid B (SAB) is the most abundant water-soluble phenolic acid active ingredient in *Salvia miltiorrhiza*, a plant in the Lamiaceae family, and is also an important material basis for its cardiovascular and cerebrovascular protective effects. SAB molecules contain multiple phenolic hydroxyl and carboxyl groups, exhibiting strong pharmacological activities such as antioxidant, anti-inflammatory, anti-endothelial injury, anti-myocardial ischemia / reperfusion injury, anti-cerebral ischemia, and anti-fibrotic effects. It shows good application potential in the prevention and treatment of coronary heart disease, stroke, liver fibrosis, and chronic inflammation-related diseases. However, SAB is a highly polar, water-soluble polyphenolic acid with poor lipid solubility and limited intestinal membrane permeability, making it difficult to effectively cross the gastrointestinal absorption barrier after oral administration. The absolute bioavailability of SAB in rats after oral administration is less than 10%, making it difficult to maintain a high level of systemic exposure, thus limiting the development of oral formulations and the full realization of its clinical efficacy. Therefore, constructing a safe, stable, and efficient oral delivery system to improve the intestinal absorption efficiency and in vivo exposure level of SAB is a key issue that urgently needs to be addressed in the modern formulation research of Danshen.
[0003] Glycyrrhizic acid (GA) is a representative triterpenoid saponin active ingredient from the legume licorice. Composed of a hydrophobic glycyrrhetinic acid core and a hydrophilic glucuronic acid group, it possesses a typical amphiphilic structure and can spontaneously form micelles or other nanoaggregates in aqueous solution. It also exhibits functions such as mucosal adhesion, inhibition of P-glycoprotein efflux, and promotion of intestinal permeability, and has been proven to serve as a natural carrier to improve the oral absorption of various drugs. However, existing glycyrrhizic acid-based co-assembly delivery systems are mainly developed for poorly soluble drugs such as cryptotanshinone and luteolin. Their assembly is driven primarily by hydrophobic interactions and cannot be directly applied to the delivery of water-soluble phenolic acids. The core interaction between SAB and GA is mainly hydrogen bonding and electrostatic interaction, which is fundamentally different from the assembly mechanism of existing systems. Therefore, whether GA and SAB can successfully co-assemble into stable nanoaggregates in nanoparticle form, and whether these assemblies can effectively improve the oral absorption of SAB and achieve cardioprotection, requires systematic research to clarify. Summary of the Invention
[0004] To address the technical problems existing in the background art, this invention provides glycyrrhizic acid-tanshinone B self-assembled nanoparticles for myocardial protection during ischemia-reperfusion, a preparation method, and applications. Using natural amphiphilic glycyrrhizic acid as the self-assembly framework, without the need for additional synthetic carriers, stable nano-aggregates spontaneously form through hydrogen bonds, electrostatic interactions, and weak hydrophobic interactions between the two molecules. These nanoparticles can effectively improve the gastrointestinal stability and intestinal membrane permeability of tanshinone B, significantly increasing its oral in vivo exposure level. Simultaneously, relying on the cardioprotective activity of glycyrrhizic acid itself, a dual pharmacodynamic synergy is achieved, providing a new formulation strategy for the oral delivery of water-soluble active ingredients from traditional Chinese medicine for cardiovascular diseases.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: A glycyrrhizic acid-tanshinone B self-assembled nanoparticle for myocardial protection during ischemia-reperfusion, comprising: glycyrrhizic acid and tanshinone B; wherein the glycyrrhizic acid and tanshinone B self-assemble into nanoparticles through intermolecular non-covalent bonding forces; wherein the glycyrrhizic acid serves as the self-assembly framework, and the tanshinone B is encapsulated within the self-assembly framework.
[0006] Further specifying, the molar ratio of glycyrrhizic acid and salvianolic acid B is (1-4):1.
[0007] Further specified, the particle size of the self-assembled nanoparticles is 105.53±5.76 nm.
[0008] A method for preparing glycyrrhizic acid-tanstansolic acid B self-assembled nanoparticles for myocardial protection during ischemia-reperfusion, comprising the following steps: Step 1: Weigh glycyrrhizic acid, add water and stir to dissolve it to obtain an aqueous phase of glycyrrhizic acid. Equilibrate the aqueous phase of glycyrrhizic acid in a water bath to obtain an equilibrated aqueous phase of glycyrrhizic acid. Step 2: Weigh out salvianolic acid B, add an aqueous ethanol solution, shake until dissolved, and obtain the organic phase of salvianolic acid B; Step 3: Add the organic phase of salvianolic acid B dropwise to the balanced aqueous phase of glycyrrhizic acid, stir, and obtain glycyrrhizic acid-salvianolic acid B self-assembled nanoparticles.
[0009] Further specifying, the molar ratio of glycyrrhizic acid to salvianolic acid B is (1-4):1.
[0010] Further specified, the stirring speed in step 1 is 500 r / min to 700 r / min; the water bath equilibration conditions in step 1 are: equilibration temperature 30℃ to 40℃, and equilibration time 3 min to 5 min.
[0011] Further specifying, the ethanol-water solution in step 2 has a mass fraction of 10%~40% (v / v), and the stirring in step 2 is vortex oscillation, with a rotation speed of 1500r / min~1700r / min.
[0012] Further specified, the dropping rate in step 3 is 0.3 mL / min to 0.5 mL / min, and the stirring conditions in step 3 are: stirring temperature 30℃ to 40℃, stirring speed 500 r / min to 700 r / min, and stirring time 30 min to 90 min.
[0013] Application of glycyrrhizic acid-tanstansolic acid B self-assembled nanoparticles for myocardial protection during ischemia-reperfusion myocardial induction in the preparation of drugs for myocardial protection.
[0014] To further specify, the myocardial protection refers to protection against myocardial ischemia-reperfusion injury.
[0015] The beneficial effects of this invention are: 1. This invention is the first to co-assemble glycyrrhizic acid (GA) and salvianolic acid B (SAB) into self-assembled nanoparticles through intermolecular non-covalent interactions. GA, composed of hydrophilic glucuronic acid groups and hydrophobic triterpenoid aglycones, serves as the self-assembly framework; SAB is the encapsulated water-soluble phenolic acid active ingredient. The two spontaneously form stable nanoaggregates through hydrogen bonding, electrostatic interactions, and weak hydrophobic interactions. The GS-NPs prepared using the optimized process have an average particle size of 105.53±5.76 nm, a PDI <0.292±0.007, and exhibit uniform particle size distribution and system stability. Characterization results by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and ¹H-NMR confirm that the two form stable nanoaggregates through non-covalent interactions such as hydrogen bonding and electrostatic interactions, with SAB dispersed amorphously within the nanoparticles. The encapsulation efficiency of GS-NPs for SAB was (77.70±0.86)%, and the drug loading was (28.44±0.43)%, demonstrating high encapsulation efficiency. Unlike existing GA-based co-assembly systems, this invention verifies for the first time the feasibility of co-assembling water-soluble phenolic acid components with GA, filling the technological gap in the application of GA self-assembly delivery systems for water-soluble components.
[0016] 2. This invention does not rely on any synthetic polymer carriers or chemical surfactants. It is entirely based on the self-assembly of two natural active ingredients, GA and SAB, to form nanoparticles. The preparation process involves only solvent mixing and stirring, requiring no heating or complex equipment, and is completed in one step with good process reproducibility. During 7 days of storage at 4℃ in the dark, the nanoparticles remained clear and transparent, without turbidity, precipitation, or stratification. The average particle size, polydispersity index (PDI), and zeta potential at each time point showed minimal changes compared to day 0, indicating that the formulation has good storage stability at 4℃, laying the foundation for its subsequent application. The all-natural ingredient design avoids the potential safety risks associated with exogenous synthetic carriers.
[0017] 3. This invention utilizes a self-assembled nanoparticle platform to encapsulate SAB using GA as a self-assembled framework. By leveraging GA's mucosal adhesion, inhibition of P-glycoprotein efflux, and promotion of intestinal permeability, it simultaneously improves the gastrointestinal stability and transmembrane permeability efficiency of SAB. Oral pharmacokinetic studies in rats showed that the time to peak concentration (T0.05) of SAB in the GS-NPs group was significantly reduced. max The absorption rate was significantly earlier (0.49 h) than that of the free SAB group (0.75 h), indicating a significantly faster absorption rate; the peak concentration (C) was also significantly higher. max The area under the curve (AUC) of the drug-time curve from 0 to t was slightly higher than that of the free SAB group. 0-t The area under the curve (AUC0-∞) for drug-time from 0 to infinity was 1.72 times and 1.81 times that of the free SAB group, and 1.61 times and 1.49 times that of the physical mixture group, respectively, indicating that the self-assembled system can significantly improve the in vivo exposure and relative bioavailability of SAB; the mean residence time from zero to t (MRT) was also significantly higher. 0-t The time to survival of SAB in vivo was prolonged (3.05±0.75 h) compared to that in the free SAB group (2.41±0.33 h), suggesting that nanoparticles can prolong the duration of SAB's survival in vivo. These results indicate that GS-NPs not only promote the early absorption of SAB but also enhance its in vivo exposure and circulatory maintenance capabilities, providing a formulation basis for the full realization of SAB's cardioprotective effect. Attached Figure Description
[0018] Figure 1 The HPLC chromatograms are of the blank solvent (A), the SAB and GA mixed reference solution (B), and the GS-NPs test solution (C) of this invention (a: SAB; b: GA).
[0019] Figure 2The following are the physicochemical characterization results of GS-NPs of the present invention and the stability evaluation results after storage at 4℃ for 7 days: (A) Particle size distribution map; (B) Zeta potential distribution map; (C) Transmission electron microscope image; (D) Ultraviolet absorption spectrum; (E) Fourier transform infrared spectrum; (F) X-ray diffraction pattern; (G) ¹H-NMR spectrum; (H) Change in Zeta potential of GS-NPs after storage at 4℃ for 7 days; (I) Change in average particle size and PDI of GS-NPs after storage at 4℃ for 7 days.
[0020] Figure 3 The above are UPLC-MS / MS chromatograms of blank plasma, SAB reference plasma solution, and plasma sample solution of this invention.
[0021] Figure 4 The mean plasma concentration-time curves of SAB in rats after gavage administration of free SAB, physical mixture (GS-Mixture), and GS-NPs according to the present invention are shown (n=6, mean±SD). Detailed Implementation
[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0023] Exemplary embodiments will now be described in detail, examples of which are illustrated in the accompanying drawings. When the following description relates to the drawings, unless otherwise indicated, the same numerals in different drawings denote the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with this disclosure. Rather, they are merely examples of methods consistent with some aspects of the invention as detailed in the appended claims.
[0024] The terminology used in this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The singular forms “a,” “the,” and “the” used in this invention and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise. It should also be understood that the term “and / or” as used herein refers to and includes any and all possible combinations of one or more of the associated listed items.
[0025] In the description of this application, it should be understood that the numerical labels before the steps do not indicate the order of the steps, but are only used to facilitate the description of this application and to distinguish each step, and therefore should not be construed as a limitation of this application.
[0026] Formulation Design Approach: Based on the oral absorption bottleneck of SABs pointed out in the background art and the limited applicability of existing GA-based co-assembly systems to water-soluble phenolic acid components, the formulation design of this invention follows the following approach: SAB's strong polarity, water solubility, and pharmacodynamic structure centered on phenolic hydroxyl groups impose specific requirements on the design of its delivery carrier: the carrier must be assembled and stabilized in an aqueous environment, and the preparation process should avoid harsh conditions such as high temperatures to protect the integrity of its phenolic hydroxyl structure; at the same time, the carrier should have a nanoscale particle size to increase the probability of contact and adhesion time with gastrointestinal epithelial cells, providing a structural basis for transmembrane absorption; in addition, the carrier should avoid introducing additional components such as oil phases or emulsifiers to avoid increasing the metabolic burden on the gastrointestinal tract.
[0027] Glycyrrhizic acid (GA) possesses a typical amphiphilic structure, spontaneously forming micelles or other nanoaggregates in aqueous solution. It also exhibits functions such as mucosal adhesion, inhibition of P-glycoprotein efflux, and promotion of intestinal permeability, theoretically meeting the aforementioned carrier design requirements. Therefore, this study used GA as a self-assembling framework to co-assemble it with SAB, constructing GA-SAB self-assembled nanoparticles (GS-NPs). The formulation process was optimized through single-factor investigation, and the feasibility of these nanoparticles improving the oral absorption of SAB was verified through physicochemical characterization and in vivo pharmacokinetic evaluation.
[0028] A glycyrrhizic acid-tanshinone B self-assembled nanoparticle for myocardial protection during ischemia-reperfusion, comprising: glycyrrhizic acid and tanshinone B; wherein the glycyrrhizic acid and tanshinone B self-assemble into nanoparticles through intermolecular non-covalent bonding forces; wherein the glycyrrhizic acid serves as the self-assembly framework, and the tanshinone B is encapsulated within the self-assembly framework.
[0029] Preferably, the molar ratio of glycyrrhizic acid to salvianolic acid B is (1-4):1.
[0030] Preferably, the particle size of the self-assembled nanoparticles is 105.53±5.76 nm.
[0031] A method for preparing glycyrrhizic acid-tanstansolic acid B self-assembled nanoparticles for myocardial protection during ischemia-reperfusion, comprising the following steps: Step 1: Weigh glycyrrhizic acid, add water and stir to dissolve it to obtain an aqueous phase of glycyrrhizic acid. Equilibrate the aqueous phase of glycyrrhizic acid in a water bath to obtain an equilibrated aqueous phase of glycyrrhizic acid. Step 2: Weigh out salvianolic acid B, add an aqueous ethanol solution, shake until dissolved, and obtain the organic phase of salvianolic acid B; Step 3: Add the organic phase of salvianolic acid B dropwise to the balanced aqueous phase of glycyrrhizic acid, stir, and obtain glycyrrhizic acid-salvianolic acid B self-assembled nanoparticles.
[0032] Preferably, the molar ratio of glycyrrhizic acid to salvianolic acid B is (1-4):1.
[0033] Preferably, the stirring speed in step 1 is 500 r / min to 700 r / min; the water bath equilibration conditions in step 1 are: equilibration temperature 30℃ to 40℃, and equilibration time 3 min to 5 min.
[0034] Preferably, the ethanol-water solution in step 2 has a mass fraction of 10% to 40% (v / v), and the stirring in step 2 is vortex oscillation with a rotation speed of 1500 to 1700 r / min.
[0035] Preferably, the dropping rate in step 3 is 0.3 mL / min to 0.5 mL / min, and the stirring conditions in step 3 are: stirring temperature 30℃ to 40℃, stirring speed 500 r / min to 700 r / min, and stirring time 30 min to 90 min.
[0036] Application of glycyrrhizic acid-tanstansolic acid B self-assembled nanoparticles for myocardial protection during ischemia-reperfusion myocardial induction in the preparation of drugs for myocardial protection.
[0037] Preferably, the myocardial protection is protection against myocardial ischemia / reperfusion injury.
[0038] The present invention will be further described below with reference to embodiments.
[0039] Example 1 This embodiment provides glycyrrhizic acid-tanstansine B self-assembled nanoparticles for myocardial protection during ischemia-reperfusion, and the preparation method includes the following steps: Step 1: Weigh 20.2 mg of glycyrrhizic acid, add ultrapure water, and dissolve it completely under magnetic stirring at 600 r / min to obtain an aqueous phase of glycyrrhizic acid. Place the aqueous phase of glycyrrhizic acid in a water bath at 35°C for 3 min to equilibrate and obtain an equilibrated aqueous phase of glycyrrhizic acid. Step 2: Weigh 8.7 mg of salvianolic acid B (molar ratio of glycyrrhizic acid to salvianolic acid B is 2:1), add 0.5 mL of 40% (v / v) ethanol aqueous solution, and vortex (1500 r / min) until completely dissolved to obtain the organic phase of salvianolic acid B; Step 3: Using a microsyringe, slowly add the organic phase of salvianolic acid B to the center of the balanced glycyrrhizic acid aqueous phase at a rate of 0.3 mL / min. After the addition is complete, stir for 60 min at 35 °C and 600 r / min to obtain glycyrrhizic acid-salvianolic acid B self-assembled nanoparticles (GS-NPs).
[0040] Example 2 This embodiment provides glycyrrhizic acid-tanstanshinone B self-assembled nanoparticles for myocardial protection during ischemia-reperfusion. The preparation method is the same as in Example 1, except that the molar ratio of glycyrrhizic acid to tanshinone B is 3:1 in this embodiment, the stirring speed in step 1 is 500 r / min, the water bath equilibration conditions in step 1 are: equilibration temperature 30 ℃, equilibration time 4 min, the ethanol aqueous solution in step 2 has a mass fraction of 30%, the stirring in step 2 is vortex oscillation, and the vortex oscillation speed is 1500 r / min, the dropping rate in step 3 is 0.4 mL / min, and the stirring conditions in step 3 are: stirring temperature 30 ℃, stirring speed 700 r / min, stirring time 30 min.
[0041] Example 3 This embodiment provides glycyrrhizic acid-tanstanshinone B self-assembled nanoparticles for myocardial protection during ischemia-reperfusion. The preparation method is the same as in Example 1, except that the molar ratio of glycyrrhizic acid to tanshinone B is 4:1 in this embodiment, the stirring speed in step 1 is 700 r / min, the water bath equilibration conditions in step 1 are: equilibration temperature 30 ℃, equilibration time 5 min, the ethanol aqueous solution in step 2 has a mass fraction of 20%, the stirring in step 2 is vortex oscillation, and the vortex oscillation speed is 1700 r / min, the dropping rate in step 3 is 0.5 mL / min, and the stirring conditions in step 3 are: stirring temperature 40 ℃, stirring speed 500 r / min, stirring time 90 min.
[0042] Example 4 This embodiment provides glycyrrhizic acid-tanstanshinone B self-assembled nanoparticles for myocardial protection during ischemia-reperfusion. The preparation method is the same as in Example 1, except that in this embodiment, the molar ratio of glycyrrhizic acid and tanshinone B is 1:1, the stirring speed in step 1 is 650 r / min, the water bath equilibration conditions in step 1 are: equilibration temperature 37 ℃, equilibration time 3 min, the ethanol aqueous solution in step 2 has a mass fraction of 10%, the stirring in step 2 is vortex oscillation, and the vortex oscillation speed is 1600 r / min, the dropping rate in step 3 is 0.4 mL / min, and the stirring conditions in step 3 are: stirring temperature 37 ℃, stirring speed 650 r / min, stirring time 80 min.
[0043] To further investigate the glycyrrhizic acid-stanshinone B self-assembled nanoparticles for myocardial protection during ischemia-reperfusion, the glycyrrhizic acid-stanshinone B self-assembled nanoparticles (GS-NPs) prepared in the examples were used for the following experiments. To accurately determine the contents of GA and SAB in GS-NPs, and the drug concentration in subsequent encapsulation efficiency, drug loading, and pharmacokinetic studies, it is necessary to first establish and validate an HPLC method for determining GA and SAB.
[0044] Experiment 1: Establishment of a methodology for determining the content of GA and SAB in glycyrrhizic acid-tanshinone B self-assembled nanoparticles (GS-NPs) 1.1 Experimental samples: glycyrrhizic acid (GA, purity ≥98%), salvianolic acid B (SAB, purity ≥98%) reference standards, GS-NPs samples.
[0045] 1.2 Experimental Methods Chromatographic conditions: The column was an Inertsil ODS-3 C18 column (250 mm × 4.6 mm, 5 μm); the mobile phase was acetonitrile-0.1% phosphoric acid aqueous solution; gradient elution: 0–5 min, 10%–35% acetonitrile; 5–15 min, 35%–55% acetonitrile; 15–23 min, 55%–65% acetonitrile; 23–25 min, 65%–10% acetonitrile; detection wavelength: 254 nm; flow rate: 1.0 mL / min; column temperature: 30 °C; injection volume: 10 μL.
[0046] Preparation of the test solution: Accurately pipette 1.0 mL of GS-NPs into an ultrafiltration centrifuge tube with a molecular weight cutoff of 10 kDa. Centrifuge at 4 ℃ and 10000 r / min for 10 min. Take an appropriate amount of the filtrate and dilute it 10 times with methanol to obtain the free drug sample solution. Separately, accurately pipette 1.0 mL of the same batch of GS-NPs, add an appropriate amount of methanol to disrupt the nanostructure, vortex mix for 2 min, and sonicate for 10 min to ensure full drug release. Then, bring the volume to 10 mL to obtain the test solution.
[0047] 1.3 Methodological Examination 1.3.1 Linearity Study: Accurately weigh SAB and GA reference standards and prepare them in methanol to a mass concentration of 1.00 mg / mL as reference stock solutions. Accurately weigh the above two reference stock solutions and add methanol to prepare a series of mixed reference solutions with SAB and GA mass concentrations of 400.00 μg / mL, 200.00 μg / mL, 100.00 μg / mL, 50.00 μg / mL, 25.00 μg / mL, and 12.50 μg / mL, respectively. Perform chromatographic analysis under the above conditions and record the peak areas (Y) of SAB and GA at each mass concentration (X). Perform linear regression of peak area (Y) against mass concentration (X).
[0048] Linear regression analysis yielded the following results: SAB regression equation Y = 70206.9X - 446127.5, r = 0.9997; GA regression equation Y = 45346.5X + 9168.0, r = 0.9995. The results indicate that SAB and GA exhibit good linearity in the range of 12.50 μg / mL to 400.00 μg / mL.
[0049] 1.3.2 Specificity test: Accurately pipette blank solvent, SAB and GA mixed reference solution, and test solution, respectively, and inject them according to the above chromatographic conditions. Compare the chromatograms.
[0050] The results are as follows Figure 1 As shown, the results indicate that there are no interfering peaks at the retention time of SAB and GA chromatographic peaks, indicating good specificity.
[0051] 1.3.3 Precision test: Accurately pipette the mixed reference solution of SAB and GA, and inject it 6 times consecutively under the above chromatographic conditions. Record the peak areas of SAB and GA, and calculate the relative standard deviation (RSD) value of the peak area of each component.
[0052] The results showed that the RSDs of the peak areas of SAB and GA were 1.16% and 1.41%, respectively, indicating that the instrument has good precision.
[0053] 1.3.4 Stability study: Take the GS-NPs test solution and inject it for detection at 0h, 2h, 4h, 8h, 12h and 24h after preparation, respectively, according to the above chromatographic conditions. Record the peak areas of SAB and GA and calculate the RSD value.
[0054] The results showed that the RSDs were 1.44% and 1.78%, respectively, indicating that the GS-NPs test solution had good stability within 24 h.
[0055] 1.3.5 Repeatability test: Take 6 portions of the same batch of GS-NPs samples, accurately pipette 1.0 mL from each portion, prepare total drug test solutions according to the above method, and inject and determine according to the above chromatographic conditions, and calculate the RSD value.
[0056] The results showed that the RSDs for the calculated mass fractions of SAB and GA were 1.54% and 1.28%, respectively, indicating that the experiment had good repeatability.
[0057] 1.3.6 Recovery Assessment: Accurately pipette 1.0 mL of the same batch of GS-NPs into 10 mL volumetric flasks. Add three levels of mixed SAB and GA standard solutions (SAB: 106 μg / mL; GA: 201 μg / mL) at low, medium, and high levels, respectively, to approximately 80%, 100%, and 120% of the measured content in the sample. Prepare three replicates for each level. Then, add an appropriate amount of methanol to disrupt the nanostructure, vortex for 2 min, and sonicate for 10 min to ensure complete drug release. After cooling to room temperature, dilute to 10 mL with methanol, shake well, filter, and inject the filtrate for analysis.
[0058] The results showed that the average recovery rate of SAB was 101.80% with an RSD of 1.79%, and the average recovery rate of GA was 100.44% with an RSD of 1.92%, indicating that this method can be used to determine the content of SAB and GA in GS-NPs.
[0059] 1.4 Results Analysis: The above results show that the established high performance liquid chromatography (HPLC) method has high specificity, high precision, good repeatability, and the recovery rate meets the requirements. It can be used for the determination of GA and SAB content in GS-NPs.
[0060] Based on the established content determination method, the effects of the molar ratio of GA to SAB, stirring time, amount of aqueous phase added, and concentration of ethanol in the organic phase on the nanoparticle size, polydispersity index (PDI), and encapsulation efficiency were further evaluated using a single-factor investigation method. This was done to determine the optimal preparation conditions for GS-NPs, ensuring uniform nanoparticle size, high encapsulation efficiency, and stable process.
[0061] Experiment 2: Preparation and process optimization of glycyrrhizic acid-tanshinone B self-assembled nanoparticles (GS-NPs) 2.1 Experimental samples: glycyrrhizic acid (GA, purity ≥98%), salvianolic acid B (SAB, purity ≥98%), anhydrous ethanol, and purified water.
[0062] 2.2 Experimental methods: Using average particle size, PDI, and encapsulation efficiency as evaluation indicators, single-factor experiments were conducted to investigate the effects of the molar ratio of glycyrrhizic acid to salvianolic acid B, stirring time, amount of aqueous phase added, and concentration of ethanol in the organic phase on the average particle size, PDI, and encapsulation efficiency of GSC-NEs. Each group was tested in triplicate.
[0063] Particle size, PDI, and encapsulation efficiency determination: Take an appropriate amount of GS-NPs sample, dilute it with pure water to a suitable concentration, and measure the particle size and PDI using a dynamic light scattering particle size analyzer at 25℃. Each sample is measured in triplicate. Encapsulation efficiency is determined by ultrafiltration centrifugation.
[0064] Investigation of the molar ratio of GA to SAB: Under the conditions of fixed aqueous phase addition of 8 mL, organic phase ethanol concentration of 30%, and stirring time of 60 min, the effect of the molar ratio of GA to SAB on the encapsulation efficiency, drug loading, average particle size and PDI of GS-NPs was investigated. The results are shown in Table 1.
[0065] Investigation of stirring time: With the conditions of fixed aqueous phase addition of 8 mL, organic phase ethanol concentration of 30%, and drug molar ratio of GA:SAB of 2:1 unchanged, the effect of stirring time on the encapsulation efficiency, drug loading, average particle size and PDI of GS-NPs was investigated. The results are shown in Table 2.
[0066] Investigation of the amount of aqueous phase added: With the drug molar ratio of GA:SAB being fixed at 2:1, the concentration of ethanol in the organic phase being 30%, and the stirring time being 60 min, the effect of the amount of aqueous phase added on the encapsulation efficiency, drug loading, average particle size, and PDI of GS-NPs was investigated. The results are shown in Table 3.
[0067] Investigation of organic phase ethanol concentration: With the conditions of fixed aqueous phase addition of 6 mL, drug molar ratio of GA:SAB of 2:1, and stirring time of 60 min unchanged, the effect of organic phase ethanol concentration on the encapsulation efficiency, drug loading, average particle size and PDI of GS-NPs was investigated. The results are shown in Table 4.
[0068] 2.3 Experimental Results The results are shown in Table 1. With increasing GA ratio, the encapsulation efficiency of GS-NPs first increased and then decreased, while the drug loading gradually decreased. The average particle size and PDI significantly increased at high GA ratios. These results indicate that an appropriate amount of GA enhances non-covalent interactions such as hydrogen bonding and hydrophobic interactions between GA and SAB, promoting the formation of smaller, more uniformly distributed self-assembled nanoparticles. Too low a GA content results in insufficient encapsulation and stabilization of SAB, leading to a lower encapsulation efficiency; excessive GA may disrupt the hydrophilic / hydrophobic balance of the system, causing nanoparticle aggregation or a wider particle size distribution. Considering all indicators, a GA to SAB molar ratio of 2:1 was determined for the subsequent preparation of GS-NPs.
[0069] Table 1. Investigation of the molar ratio of GA to SAB drugs ( ±s, n=3) The results are shown in Table 2. With the extension of stirring time, the encapsulation efficiency and drug loading of GS-NPs showed a trend of first increasing and then decreasing, while the average particle size and PDI showed a trend of first decreasing and then increasing. When the stirring time is short, the dispersion of the organic phase in the aqueous phase is not sufficient, and the contact, collision, and self-assembly processes between GA and SAB molecules have not reached complete equilibrium, resulting in insufficient nanoparticle formation and a wide particle size distribution. After appropriately extending the stirring time, the system is more uniformly mixed, which is conducive to the diffusion of SAB from the organic phase to the aqueous phase, and the formation of more stable nano-aggregates with GA through non-covalent interactions such as hydrogen bonding and hydrophobic interactions. Therefore, the encapsulation efficiency and drug loading are improved, the particle size is reduced, and the PDI is decreased. When the stirring time continues to be extended, the nanoparticles already formed in the system may be affected by continuous shearing and molecular rearrangement. Some of the weakly bound SABs dissociate, and the collision opportunities between nanoparticles increase, making secondary aggregation or a wider particle size distribution more likely, which is manifested as an increase in average particle size and PDI. Taking all indicators into account, GS-NPs showed better drug loading performance, smaller particle size, and more uniform distribution after stirring for 60 min. Therefore, the stirring time was determined to be 60 min for the subsequent preparation of GS-NPs.
[0070] Table 2. Investigation of stirring time ( ±s, n=3) The results are shown in Table 3. With the increase of aqueous phase addition, the encapsulation efficiency and drug loading of GS-NPs showed a trend of first increasing and then decreasing, while the average particle size generally showed an increasing trend, and the PDI remained within a relatively acceptable range. A suitable aqueous phase volume is beneficial for the rapid dispersion of the organic phase in the aqueous phase, reducing local concentration differences and promoting the self-assembly of GA and SAB in a more uniform dispersion environment, thereby improving the nanoparticle encapsulation effect and dispersion uniformity. When the aqueous phase addition is too high, the system dilution increases, the effective collision and binding probability between GA and SAB molecules decreases, and the exposure of SAB in the aqueous phase increases, which is not conducive to its stable encapsulation, leading to a decrease in encapsulation efficiency and drug loading, accompanied by an increase in particle size. Considering all indicators, the aqueous phase addition amount was determined to be 6 mL for the subsequent preparation of GS-NPs.
[0071] Table 3 Investigation of Aqueous Phase Addition Amount ( ±s, n=3) The results are shown in Table 4. With increasing ethanol concentration in the organic phase, the encapsulation efficiency and drug loading of GS-NPs generally increased, indicating that appropriately increasing the ethanol concentration is beneficial for improving the solubility of SAB in the organic phase, reducing uneven drug precipitation during dropwise addition, and thus promoting sufficient contact between SAB and GA and their participation in self-assembly. At lower ethanol concentrations, the organic phase has insufficient solubility for SAB, and the drug easily precipitates rapidly after entering the aqueous phase, resulting in lower encapsulation efficiency and a relatively wide particle size distribution. With increased ethanol concentration, the desolvation process during the mixing of the organic and aqueous phases becomes more suitable, which is beneficial for forming more stable GA-SAB self-assembled aggregates. The increased average particle size at some intermediate concentrations may be related to continued particle growth or local aggregation after nucleation, but the PDI has decreased to a reasonable range, indicating improved uniformity of the system's particle size distribution. Considering all indicators, an organic phase ethanol concentration of 40% was determined for the subsequent preparation of GS-NPs.
[0072] Table 4. Investigation of ethanol concentration in the organic phase ( ±s, n=3) 2.4 Results Analysis The results of the single-factor analysis above indicate that the optimal formulation conditions are: a GA to SAB molar ratio of 2:1. The optimal process conditions are: a stirring time of 60 min, an aqueous phase addition of 6 mL, and an organic phase ethanol concentration of 40%.
[0073] Based on the determination of the optimal preparation process, in order to confirm whether GS-NPs were successfully formed and their microstructural characteristics, GS-NPs were systematically characterized from multiple perspectives, including particle size distribution, morphological observation, intermolecular interactions and crystal state, providing structural basis for subsequent explanation of their improved oral absorption effect.
[0074] Experiment 3: Physicochemical characterization of glycyrrhizic acid-tanshinone B self-assembled nanoparticles (GS-NPs) 3.1 Experimental Samples: The glycyrrhizic acid-tanshinone B self-assembled nanoparticles (GS-NPs) prepared in the embodiments of the present invention were freeze-dried to obtain GS-NPs lyophilized powder.
[0075] 3.2 Particle size distribution, PDI and zeta potential determination 3.2.1 Experimental Methods: 100 μL of GS-NPs was diluted to 1 mL and then analyzed using a Malvern Zetasizer Nano ZS90 nanoparticle size and zeta potential analyzer at 25 ℃. The average particle size, PDI, and zeta potential were measured in triplicate for each sample, and the particle size distribution was recorded (see [reference]). Figure 2 A) and Zeta potential distribution map (see A) Figure 2 B).
[0076] 3.2.2 Experimental Results: (e.g.) Figure 2 As shown in Figure A, the particle size distribution of GS-NPs is relatively concentrated, such as... Figure 2 As shown in Figure B, the Zeta potential exhibits a single-peak distribution, indicating that the prepared nanoparticles have good dispersibility and the system possesses colloidal stability.
[0077] 3.3 Observation of the morphology of GS-NPs by transmission electron microscopy (TEM) 3.3.1 Experimental Method: Take an appropriate amount of GS-NPs, dilute it 10 times with ultrapure water, and shake well. Add 10 μL of the diluted solution to a 300-mesh copper mesh supporting a carbon film, allow it to stand for 5 min for adsorption, then remove excess liquid; add 1% phosphotungstic acid aqueous solution for negative staining for 3 min, air dry at room temperature for 15 min, and observe and photograph the morphology of the nanoparticles under a transmission electron microscope after natural air drying. Test conditions: accelerating voltage 200 kV, results are shown in […]. Figure 2 C.
[0078] 3.3.2 Experimental Results: TEM images as follows Figure 2 As shown in Figure C, the GS-NPs are basically spherical with clear boundaries and a particle size of approximately (105.53±5.76) nm. TEM results further confirm that the GS-NPs are uniform spherical nanostructures.
[0079] 3.4 Ultraviolet Absorption Spectroscopy Analysis 3.4.1 Experimental Methods: GA, SAB, and GS-NPs test solutions were prepared separately to ensure consistent mass concentrations of the active ingredients in each solution. Using ultrapure water as a blank, a full-wavelength UV-Vis scan was performed in the wavelength range of 200–600 nm at a medium scanning speed (UV-2600 instrument) with a slit width of 2 nm. The UV absorption spectra were recorded.
[0080] 3.4.2 Experimental Results: The results are shown in [the table below]. Figure 2 D. Compared with GA and SAB solutions, the characteristic absorption peak of GS-NPs shifted and the absorption intensity changed. The above results indicate that there is an intermolecular interaction between GA and SAB during self-assembly, suggesting that GA and SAB form a non-covalent bond interaction in the nanoparticles.
[0081] 3.5 Fourier transform infrared spectroscopy (FT-IR) analysis 3.5.1 Experimental Method: Take appropriate amounts of GA, SAB, a physical mixture (GA to SAB ratio is the same as GS-NPs), and GS-NPs lyophilized powder. All samples and potassium bromide should be thoroughly dried. Grind each sample with potassium bromide at a mass ratio of 1:100 until homogeneous. Compress into tablets and test immediately. Use pure potassium bromide tablets as a blank background.
[0082] FT-IR testing conditions: 32 scans for both background and sample, resolution 4 cm⁻¹ -1 The Fourier transform infrared spectrum is shown below. Figure 2 E.
[0083] 3.5.2 Experimental Results: (e.g.) Figure 2 As shown in E, GA is at 3400 cm. -1 A broad -OH stretching vibration peak appears nearby, at 1655.29 cm⁻¹. -1 A C=O / C=C related vibrational peak appears at 1045.99 cm⁻¹. -1 The CO / COC stretching vibration peak appears at 3400-2500 cm⁻¹. The SAB peak is located at 3400-2500 cm⁻¹. -1 A relatively broad -OH absorption band is observed within the range, at 1725.47 cm⁻¹. -1 A C=O stretching vibration peak appears at 1610.63 cm⁻¹, belonging to the carboxyl or ester carbonyl group. -1 A vibrational peak of the aromatic ring skeleton appears at 1112.98 cm⁻¹. -1 1073.11 cm -1 A CO stretching vibration peak appears at 3397.07 cm⁻¹. After the formation of GS-NPs, the peak is observed at 3397.07 cm⁻¹. -1A broad peak of -OH stretching vibration appears at 1725.47 cm⁻¹ in SAB. -1 The characteristic peak of C=O at this point is significantly weakened, and the peak at 1655.29 cm⁻¹ in GA is also significantly weakened. -1 The absorption peak near 1610.63 cm⁻¹ in SAB appears at 1626.58 cm⁻¹ in GS-NPs. -1 The peak shape changed at 1085.86 cm⁻¹, and the CO / COC related absorption peaks at 1020.46 cm⁻¹ also changed.
[0084] The results show that GA and SAB may combine with each other through non-covalent interactions such as hydrogen bonds during self-assembly to form GS-NPs; and no obvious new characteristic absorption peaks were observed, indicating that the main chemical structures of the two have not changed significantly.
[0085] 3.6 X-ray powder diffraction analysis 3.6.1 Experimental method: Take appropriate amounts of GA, SAB, lyophilization protectant (mannitol) and GS-NPs lyophilized powder respectively, place them in the sample cell, press the glass slide flat, scrape off the excess sample outside the groove, and then scan it under an X-ray powder diffractometer to analyze the crystal form changes in the sample.
[0086] 3.6.2 Experimental Results: The results are shown in [the table below]. Figure 2 F and GA exhibit multiple diffraction peaks in the 2θ 10°–30° range, indicating certain crystal characteristics. SAB mainly shows broad, diffuse peaks in the 2θ 15°–25° range, without any obvious sharp diffraction peaks, suggesting low crystallinity or that it exists primarily in an amorphous state. Compared to GA and SAB, GS-NPs show a series of sharper diffraction peaks in the 2θ 15°–25° range, and their peak shapes and positions are not a simple superposition of the characteristic peaks of the two, indicating that the solid state of GA and SAB changes after self-assembly.
[0087] The above results indicate that the formation of GS-NPs differs from the physical mixing of drug monomers. It is related to molecular rearrangement and ordered aggregation mediated by non-covalent interactions such as hydrogen bonding and hydrophobic interactions between GA and SAB, thus forming a self-assembled nanosystem with certain ordered structural characteristics. XRD results confirm the successful construction of GS-NPs from the perspective of crystal structure changes.
[0088] 3.7 Proton NMR Spectroscopy Analysis 3.7.1 Experimental Method: Dissolve appropriate amounts of lyophilized GA, SAB, and GS-NPs powders in deuterated reagents, mix thoroughly, and transfer to an NMR tube. Maintain a sample column height of approximately 4-5 cm and a volume of approximately 500-600 μL. Place the NMR tube in the NMR spectrometer and perform measurements after the instrument has completed field locking, tuning, and shimming. 1 H NMR spectrum.
[0089] 3.7.2 Experimental Results: The results are as follows Figure 2 G and GA exhibit multiple proton signals in the δ 0.5–2.0 and δ 3.0–5.5 ranges, respectively attributed to triterpenoid nucleus methyl, aliphatic hydrogen, and glycosyl proton signals. SAB shows characteristic proton signals of aromatic rings and alkenes in the δ 6.0–8.0 range, and oxymethylene or methine-related proton signals in the δ 3.0–5.0 range. Compared to GA and SAB, most characteristic proton signals in GS-NPs are significantly weakened or almost disappeared; except for a residual water peak near δ 4.7, no obvious characteristic peaks of free GA and SAB are observed.
[0090] The above results indicate that the molecular motion of GA and SAB is restricted after self-assembly, and some protons are embedded inside the nano-aggregates or affected by intermolecular interactions, resulting in the broadening, attenuation or even disappearance of the NMR signal, further confirming the existence of non-covalent interactions such as intermolecular hydrogen bonds between GA and SAB.
[0091] Based on the confirmation of successful nanoparticle formation, in order to evaluate the encapsulation efficiency of GS-NPs for SAB, ultrafiltration centrifugation was used to separate free drug and nanoparticles, and the encapsulation efficiency and drug loading of SAB were determined.
[0092] Experiment 4: Encapsulation efficiency and drug loading of glycyrrhizic acid-tanshinone B self-assembled nanoparticles (GS-NPs) 4.1 Experimental Samples: Glycyrrhizic acid-tanshinone B self-assembled nanoparticles (GS-NPs) prepared by the optimal process of this invention. 4.2 Experimental Methods: Accurately pipette 1.0 mL of GS-NPs into an ultrafiltration centrifuge tube with a molecular weight cutoff of 10 kDa. Centrifuge at 4 ℃ and 10000 r / min for 10 min. Take an appropriate amount of filtrate, dilute it 10 times with methanol, and determine the free SAB mass according to the chromatographic conditions in section "1.2". Calculate the free SAB mass based on the standard curve and dilution factor, and record it as M1. Separately, accurately pipette 1.0 mL of the same batch of GS-NPs, add an appropriate amount of methanol to destroy the nanostructure, vortex mix for 2 min, and sonicate for 10 min to ensure full drug release. Then, dilute to 10 mL with methanol, shake well, filter through a 0.22 μm microporous membrane, and determine the total SAB mass M2 and total GA mass M3 based on the standard curve. Calculate the SAB encapsulation efficiency (EE) and drug loading (DL) using the following formula: EE (%) = [(M2-M1) / M2] × 100% DL (%)=[(M2-M1) / (M2+M3)]×100% 4.3 Experimental Results The results showed that the encapsulation efficiency of SAB in GS-NPs was 77.08±0.69%, and the drug loading was 28.23±0.60%. These results indicate that the prepared GS-NPs can effectively encapsulate SAB, exhibiting good encapsulation performance and drug loading capacity. The results also demonstrate that the self-assembled nanoparticles of this invention possess high encapsulation efficiency and drug loading for both active ingredients, providing a formulation basis for oral delivery.
[0093] Based on the confirmation that GS-NPs have high encapsulation efficiency, in order to examine their stability under actual storage conditions and provide a basis for their subsequent application and storage conditions, the changes in nanoparticle size, PDI, encapsulation efficiency and drug content were investigated over 6 months at 4℃.
[0094] Experiment 5: Storage Stability Evaluation 5.1 Experimental Methods: GS-NPs prepared according to the optimal process were stored in a light-protected, sealed container at 4 ℃. Samples were taken at regular intervals of 0d, 1d, 2d, 3d, 4d, 5d, 6d, and 7d, with 100 μL of sample taken each time. After appropriate dilution, the average particle size, PDI, and Zeta potential were measured. At the same time, the appearance of the samples was visually observed, and the presence of turbidity, precipitation, layering, or discoloration was recorded. The results are shown in Table 5.
[0095] 5.2 Experimental Results: GS-NPs remained clear and transparent throughout the 7-day period at 4 ℃ in the dark, without any turbidity, precipitation, or stratification. Figure 2 Figures H and 2I show the changes in average particle size, PDI, and Zeta potential of GS-NPs stored at 4 ℃ for 7 days. The changes in average particle size, PDI, and Zeta potential at each time point compared to 0 days are small, indicating that the formulation has good storage stability at 4 ℃.
[0096] Table 5. Stability data of GS-NPs at 4 ℃ for 7 days ( ±s, n=3) Based on the confirmation that GS-NPs can be successfully prepared, have a well-defined structure, high loading efficiency, and are stable in storage, in order to verify whether they can improve the oral bioavailability of SAB, an ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS / MS) method for the determination of GA and SAB in plasma was established, and the pharmacokinetic behavior of free SAB, physical mixtures, and GS-NPs after gavage administration in rats was compared.
[0097] Experiment 6: Oral pharmacokinetic study of glycyrrhizic acid-tanshinone B self-assembled nanoparticles (GS-NPs) in rats 6.1 Experimental Methods Chromatographic and mass spectrometric conditions: The chromatographic column was an ACQUITY UPLC BEH C18 column (100 mm × 2.1 mm, 1.7 μm); the mobile phase was 0.1% formic acid aqueous solution (A) - acetonitrile (B), with gradient elution: 0.00 min, 90% A; 0.00–0.68 min, 90%–80% A; 0.68–1.63 min, 80%–65% A; 1.63–2.45 min, 65%–45% A; 2.45–2.86 min, 45%–30% A; 2.86–3.80 min, 30% A; 3.80–4.10 min, 30%–90% A; 4.10–5.60 min, maintenance 90% A. The flow rate was 0.60 mL / min; the column temperature was 40 ℃; and the injection volume was 5 μL. Detection was performed using ESI negative ion mode and multiple reaction monitoring (MRM) mode. The IonSpray Voltage was -4500 V, the ion source temperature was 500 °C, the nebulizing gas (GS1) pressure was 60 psi, the heating gas (GS2) pressure was 50 psi, the curtain gas pressure was 20 psi, the collision gas was nitrogen, and the CAD was set to Medium. The quantitative ion pair for SAB was m / z 717.0→519.0, the declustering voltage (DP) was -80 V, and the collision energy (CE) was 28 V. The detection ion pair for the internal standard chloramphenicol was m / z 323.0→152.0, the DP was +70 V, and the CE was 20 V.
[0098] Administration and blood collection protocols: Free SAB solutions, the physical mixture of GA and SAB prepared in Example 1 (GS-Mix), and GS-NPs were prepared by gavage using ultrapure water, all measured in SAB form. Twenty-four SD rats (after acclimatization) were randomly divided into four groups of six each: free SAB group, GS-Mix group, and GS-NPs group. After weighing, each group was administered the drug by gavage at a dose of 100 mg / kg (based on SAB). Rats were fasted for 12 hours prior to administration but allowed free access to water. At 0.083 h, 0.167 h, 0.25 h, 0.5 h, 1 h, 2 h, 4 h, 6 h, 8 h, and 10 h post-administration, rats were immobilized, and approximately 0.5 mL of blood was collected from the retro-orbital venous plexus using a capillary glass tube. The blood was rapidly transferred to centrifuge tubes pre-filled with heparin sodium and gently inverted to prevent clotting. After the blood sample was left to stand at room temperature for 30 min, it was centrifuged at 3500 r / min for 10 min to separate the supernatant plasma, which was then stored in an ultra-low temperature freezer at -80 ℃ for later use.
[0099] Plasma sample preparation: Accurately weigh chloramphenicol reference standard and prepare an internal standard solution with a mass concentration of 10 μg / mL using methanol. Accurately pipette 100 μL of rat plasma sample (thawed at room temperature) into an EP tube, add 40 μL of internal standard solution and 260 μL of methanol sequentially, vortex mix for 1 min, and centrifuge at 13000 r / min for 10 min at 4 ℃. Collect the supernatant and filter it through a 0.22 μm microporous membrane to obtain the test plasma sample solution.
[0100] 6.2 Methodological Examination 6.2.1 Linearity Assessment: Blank rat plasma was collected and different concentrations of SAB standard working solution were added to prepare a series of matrix-spiked plasma controls. Samples were processed according to the plasma sample processing method described above before injection and determination.
[0101] Linear regression analysis was performed with the plasma SAB concentration (X) as the abscissa and the peak area ratio of SAB to internal standard (Y) as the ordinate, and the standard curve regression equation was obtained as Y=0.0004X-0.0048, r=0.9991.
[0102] The results showed that SAB exhibited good linearity in the range of 5.6–1120.0 ng / mL. The lowest calibration concentration was used as the limit of quantitation (LLOQ) of the method, requiring a signal-to-noise ratio (S / N) ≥ 10, and precision and accuracy deviations within ±20%.
[0103] 6.2.2 Specificity Assessment: Blank plasma samples were taken and processed according to the plasma sample processing method described above to prepare blank plasma sample solutions. Separately, blank plasma samples with added reference standards and actual plasma samples after drug administration were taken, processed in the same manner, and then injected and analyzed according to the chromatographic and mass spectrometric conditions described above. The results are shown in the table below. Figure 3 Chromatograms of blank plasma, SAB reference plasma solution, and plasma sample solution obtained by ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS / MS).
[0104] The results are as follows Figure 3 The results show that blank plasma has no endogenous interference peaks at the retention times of SAB and internal standard, and the SAB peak shape is good and symmetrical, indicating that the method has good specificity.
[0105] 6.2.3 Precision test: Take plasma quality control (QC) samples containing SAB at concentrations of 10.0 ng / mL (low), 50.0 ng / mL (medium), and 500.0 ng / mL (high), with 6 samples of each concentration. Process the samples according to the above method and then inject them for determination. Perform 6 consecutive measurements on the same day.
[0106] The results showed that the intra-day precision RSDs of the peak area ratio of SAB to internal standard were 3.43%, 6.47%, and 2.99%, respectively; the inter-day precision RSDs of the measurements taken once a day for 3 consecutive days were 13.34%, 6.13%, and 5.76%, respectively.
[0107] The results showed that the intraday and interday relative standard deviations (RSD) of SAB at low, medium and high concentration levels were all below 13.00%, indicating that the method has good precision and meets the requirements of biological sample analysis methodology.
[0108] 6.2.4 Stability Study: Plasma QC samples at three concentration levels of SAB (10.0 ng / mL, low, 50.0 ng / mL, medium, and 500.0 ng / mL, high) were prepared in parallel (6 replicates per concentration) to assess room temperature stability and freeze-thaw stability. Samples were placed at room temperature for 24 h before analysis to evaluate room temperature stability; additional samples were subjected to three freeze-thaw cycles before analysis to evaluate freeze-thaw stability. All samples were processed and analyzed according to the above method, and the RSD of the SAB to internal standard peak area ratio was used to evaluate stability.
[0109] The results showed that after 24 h at room temperature, the RSDs of the peak area ratios of low, medium and high concentration QC samples were 2.27%, 8.47% and 3.10%, respectively; after three repeated freeze-thaw cycles, the RSDs were 3.60%, 4.84% and 5.33%, respectively.
[0110] The above results are all less than 15%, indicating that SAB has good stability in plasma and good stability after sample processing.
[0111] 6.2.5 Extraction Recovery Assessment: Six aliquots of SAB reference solutions at three concentration levels (10.0 ng / mL (low), 50.0 ng / mL (medium), and 500.0 ng / mL (high)) were prepared according to the above method, and the peak area was measured under the corresponding chromatographic and mass spectrometric conditions (denoted as A). An equal volume of blank plasma was also prepared, and after protein precipitation and centrifugation as described above, the same concentration of SAB reference solution was added to the supernatant, and the peak area was measured (denoted as B). The extraction recovery rate was calculated as A / B.
[0112] The results showed that the extraction recoveries of low, medium, and high concentrations of SAB were 102.16%, 95.30%, and 97.09%, respectively, indicating that the method has good extraction efficiency and can meet the requirements of biological sample analysis.
[0113] 6.2.6 Matrix effect investigation: Three reference solutions of SAB at low, medium, and high mass concentrations were taken, diluted with methanol to the corresponding concentrations, and injected under the same chromatographic and mass spectrometric conditions to determine the peak area (denoted as C). The matrix effect was calculated as B / C.
[0114] The results showed that the matrix effect of low, medium, and high-quality SAB was 101.32%, 96.05%, and 89.62%, respectively, indicating that the matrix had little effect on the determination and could be used for the determination of SAB plasma concentration.
[0115] 6.2.7 Pharmacokinetic Results Examination The SAB content in plasma samples at each blood collection time point was determined according to the above chromatographic and mass spectrometric conditions. Blood drug concentration-time curves were plotted for the free SAB, GS-Mixture, and GS-NPs groups. The results are shown in [Figure Number]. Figure 4 .
[0116] The data were fitted using DAS 2.0 software, and the pharmacokinetic parameters of each group of samples were calculated using the non-compartmental model statistical moment method. The results are shown in Table 6.
[0117] Pharmacokinetic analysis showed that, Figure 4 As shown, the GS-NPs group reached its peak concentration at 0.49 h, significantly earlier than the SAB group at 0.75 h. Its peak concentration time (T0) was also significantly shorter. max The peak concentration (C0.65) was approximately 0.65 times that of the free SAB group and also earlier than that of the GS-Mix group, indicating that the binary self-assembly system can accelerate the absorption rate of SAB. max In terms of pharmacokinetic parameters, the GS-NPs group was slightly higher than the SAB group, with a larger area under the curve (AUC) from time 0 to time t. 0-t ) and the area under the curve (AUC) of the drug-time curve from 0 to infinity. 0-∞ In terms of the GS-NPs group, the levels were approximately 1.72 times and 1.81 times that of the SAB group, and 1.61 times and 1.49 times that of the GS-Mix group, indicating that this self-assembly system can improve the exposure and relative bioavailability of SAB in vivo.
[0118] Meanwhile, the MRT of the GS-NPs group 0-t The duration of in vivo maintenance was 3.05 ± 0.75 h, higher than that of the SAB group (2.41 ± 0.33 h), indicating an increased duration of maintenance in vivo during the observation period; while T... 1 / 2 Slightly lower than the SAB group, indicating a slightly faster terminal elimination phase. Overall, GS-NPs not only promoted early absorption of SAB but also enhanced maintenance and overall exposure in vivo.
[0119] Table 6. Main pharmacokinetic parameters of free SAB, binary self-assembled nanosolutions and physical mixtures In summary, this invention successfully constructed GA-SAB self-assembled nanoparticles (GS-NPs). The optimal preparation conditions were determined through single-factor process optimization. Characterization results, including particle size, PDI, Zeta potential, TEM, FTIR, XRD, and ¹H-NMR, confirmed the successful formation of GS-NPs and their intermolecular non-covalent interactions. Oral pharmacokinetic results in rats showed that the Tg of SAB in the GS-NPs group... max The AUC was significantly shortened from 0.75 h in the free SAB group to 0.49 h. 0-t and AUC 0-∞ The levels were increased to 1.72 times and 1.81 times that of the free SAB group, respectively, and the MRT was also increased. 0-t The in vivo absorption time was extended from 2.41 h to 3.05 h, indicating that the self-assembled nanoparticles can significantly accelerate the absorption rate of SAB, increase its in vivo exposure level, and prolong its in vivo maintenance time. Meanwhile, the GS-NPs preparation process is simple, requiring no synthetic excipients or complex equipment, and exhibits good stability after 6 months of storage at 4°C, demonstrating good potential for clinical translation. These results indicate that the binary co-assembly of GA and SAB to form self-assembled nanoparticles can effectively improve the oral absorption efficiency and in vivo pharmacokinetic behavior of SAB, providing a new formulation strategy and experimental basis for the oral delivery of water-soluble active ingredients from traditional Chinese medicine.
Claims
1. A glycyrrhizic acid-tanstansine B self-assembled nanoparticle for myocardial protection during ischemia-reperfusion, characterized in that, include: Glycyrrhizic acid and salvianolic acid B; the glycyrrhizic acid and salvianolic acid B self-assemble into nanoparticles through intermolecular non-covalent bonding forces; The glycyrrhizic acid serves as a self-assembling framework, and the salvianolic acid B is encapsulated within the self-assembling framework.
2. The glycyrrhizic acid-tanstansolic acid B self-assembled nanoparticles for myocardial protection during ischemia-reperfusion according to claim 1, characterized in that, The molar ratio of glycyrrhizic acid to salvianolic acid B is (1-4):
1.
3. The glycyrrhizic acid-tanstansolic acid B self-assembled nanoparticles for myocardial protection during ischemia-reperfusion according to claim 1, characterized in that, The particle size of the self-assembled nanoparticles is 105.53 ± 5.76 nm.
4. A method for preparing glycyrrhizic acid-tanstansolic acid B self-assembled nanoparticles for myocardial protection during ischemia-reperfusion, according to any one of claims 1-3, characterized in that, Includes the following steps: Step 1: Weigh glycyrrhizic acid, add water and stir to dissolve it to obtain an aqueous phase of glycyrrhizic acid. Equilibrate the aqueous phase of glycyrrhizic acid in a water bath to obtain an equilibrated aqueous phase of glycyrrhizic acid. Step 2: Weigh out salvianolic acid B, add an aqueous ethanol solution, shake until dissolved, and obtain the organic phase of salvianolic acid B; Step 3: Add the organic phase of salvianolic acid B dropwise to the balanced aqueous phase of glycyrrhizic acid, stir, and obtain glycyrrhizic acid-salvianolic acid B self-assembled nanoparticles.
5. The method for preparing glycyrrhizic acid-tanstansolic acid B self-assembled nanoparticles for myocardial protection during ischemia-reperfusion according to claim 4, characterized in that, The molar ratio of glycyrrhizic acid to salvianolic acid B is (1-4):
1.
6. The method for preparing glycyrrhizic acid-tanstansolic acid B self-assembled nanoparticles for myocardial protection during ischemia-reperfusion according to claim 4, characterized in that, The stirring speed in step 1 is 500 r / min to 700 r / min; the water bath equilibration conditions in step 1 are: equilibration temperature 30℃ to 40℃, equilibration time 3 min to 5 min.
7. The method for preparing glycyrrhizic acid-tanstansolic acid B self-assembled nanoparticles for myocardial protection during ischemia-reperfusion according to claim 4, characterized in that, The ethanol-water solution in step 2 has a mass fraction of 10%~40% (v / v), and the stirring in step 2 is vortex oscillation with a rotation speed of 1500r / min~1700r / min.
8. The method for preparing glycyrrhizic acid-tanstansolic acid B self-assembled nanoparticles for myocardial protection during ischemia-reperfusion according to claim 4, characterized in that, The dropping rate in step 3 is 0.3 mL / min to 0.5 mL / min, and the stirring conditions in step 3 are: stirring temperature 30℃ to 40℃, stirring speed 500 r / min to 700 r / min, and stirring time 30 min to 90 min.
9. The use of glycyrrhizic acid-tanshinone B self-assembled nanoparticles for ischemia-reperfusion myocardial protection prepared by the method of preparing glycyrrhizic acid-tanshinone B self-assembled nanoparticles for ischemia-reperfusion myocardial protection according to any one of claims 1-3, or according to any one of claims 4-8, in the preparation of drugs for myocardial protection.
10. The application according to claim 9, characterized in that, The aforementioned myocardial protection refers to protection against myocardial ischemia-reperfusion injury.